2021
DOI: 10.1007/s12028-021-01305-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Increased Hemoglobin on Spontaneous Intracerebral Hemorrhage

Abstract: Background Studies of the impact of increased hemoglobin on spontaneous intracerebral hemorrhage (ICH) are limited. The present study aimed to explore the effect of increased hemoglobin on ICH. Methods A retrospective single-center study using medical records from a database processed by univariate and multivariate analyses was performed in the People’s Hospital of Tibet Autonomous Region in Lhasa, Tibet, China. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Previous studies have identified that hemoglobin at both extremes (ie, low and high hemoglobin) has been linked to poor cardiovascular and cerebrovascular (including ICH) outcomes. 9,10,12–16,28–30 In this regard, even our own data may similarly suggest a U-shaped relationship of hemoglobin with clinical ICH outcomes. If our hemoglobin-DWI lesion associations are truly related to high hemoglobin concentrations, it could be posited from this and other work that hemoglobin has separate, multimodal pathophysiologic impacts on clinical outcomes at both extremes after ICH, 13,14,16,29 as has been reported in other disease processes.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Previous studies have identified that hemoglobin at both extremes (ie, low and high hemoglobin) has been linked to poor cardiovascular and cerebrovascular (including ICH) outcomes. 9,10,12–16,28–30 In this regard, even our own data may similarly suggest a U-shaped relationship of hemoglobin with clinical ICH outcomes. If our hemoglobin-DWI lesion associations are truly related to high hemoglobin concentrations, it could be posited from this and other work that hemoglobin has separate, multimodal pathophysiologic impacts on clinical outcomes at both extremes after ICH, 13,14,16,29 as has been reported in other disease processes.…”
Section: Discussionmentioning
confidence: 67%
“…9,10,12–16,28–30 In this regard, even our own data may similarly suggest a U-shaped relationship of hemoglobin with clinical ICH outcomes. If our hemoglobin-DWI lesion associations are truly related to high hemoglobin concentrations, it could be posited from this and other work that hemoglobin has separate, multimodal pathophysiologic impacts on clinical outcomes at both extremes after ICH, 13,14,16,29 as has been reported in other disease processes. 9,11,12,28,30 Specifically, it could be speculated at lower baseline hemoglobin concentrations, patients with ICH are at risk for acute hematoma expansion and larger ICH volumes.…”
Section: Discussionmentioning
confidence: 67%